Employer Brand Image Dimensionality - Mardiyanto, Agung (Jobmark: Journal of Branding and Marketing Communication, 2021)
This article examines the dimensions of employer brand image based on Wijaya's theory of Dimensions of Brand Image. By using the Theory Adaptation approach through literature study and intertextual validation, this article proposes several constructs in the dimensions of employer brand identity, personality, association, behavior, and competence as dimensions of employer brand image. Employer branding practices and the implications of employer brand image dimensionality are thoroughly reviewed with theoretical discussions. This study guides employers in implementing brand image strategies and is an essential reference for future research. Researchers and practitioners can measure whether employers already have a solid brand image to attract job seekers and maintain employee loyalty. The more positive and robust these dimensions are in the eyes of the public, the stronger and more positive the company's image as an employer will be.